1990
DOI: 10.1111/j.1432-1033.1990.tb19124.x
|View full text |Cite
|
Sign up to set email alerts
|

A 19F‐NMR study of 3‐fluoro‐4‐demethoxydaunomycin intercalation complexes with the hexanucleotide d(CTGCAG)2

Abstract: Equilibrium systems containing intercalation complexes formed between the novel anthracycline drug, 3‐fluoro‐4‐demethoxydaunomycin (3FD), and the hexanucleotide duplex d(CTGCAG)2 have been studied by 19FNMR spectroscopy. Solutions containing a 1:1 molar ratio of 3FD/d(CTGCAG)2 gave four 19F signals which have been assigned to each of four possible intercalation isomers for the 1:1 3FD · d(CTGCAG)2 complex, which we denote by [d(CTGCAG)2][3FD]; these were where 3FD bound between the 5′‐CT‐3′,5′‐TG‐3′, 5′‐GC‐3′ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…At higher NaCl concentrations, where the duplex is significantly more stable, the results of the 'H NMR study of 3FDd(CTGCAG), complex showed that the structure corresponding to isomer 1 in Fig. 3 exhibited the fastest 3FD dissociation rate [13]. This is consistent with other studies which have shown that the individual base pair melting temperature progressively increases in going from the terminal base pairs to the central residues of an oligonucleotide [14,15].…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…At higher NaCl concentrations, where the duplex is significantly more stable, the results of the 'H NMR study of 3FDd(CTGCAG), complex showed that the structure corresponding to isomer 1 in Fig. 3 exhibited the fastest 3FD dissociation rate [13]. This is consistent with other studies which have shown that the individual base pair melting temperature progressively increases in going from the terminal base pairs to the central residues of an oligonucleotide [14,15].…”
Section: Resultssupporting
confidence: 89%
“…3. These conclusion are strongly supported by the results of our earlier study [6] of the binding of 3FD with the hexanucleotide d(CTGCAG),. In an analogous fashion, four 19F resonances were also observed and assigned to the four possible intercalation isomers; that is where the 3FD bound between the S-CT-3', S-TG-3', 5'-GC-3' and 5'-CA-3' with the drug sugar moiety lying in the minor groove and pointed in the 3' direction in each case.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations